2022
DOI: 10.1128/cmr.00027-21
|View full text |Cite
|
Sign up to set email alerts
|

Updated Review onNocardiaSpecies: 2006–2021

Abstract: This review serves as an update to the previous Nocardia review by Brown-Elliott et al. published in 2006 (B. A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 293 publications
0
41
0
Order By: Relevance
“…Additionally, Nocardia may be related to specific activities and exposures, most notably outdoor activities such as gardening. 34 Another consideration is possible differences in risk between those who did and did not undergo transplantation, leading to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Nocardia may be related to specific activities and exposures, most notably outdoor activities such as gardening. 34 Another consideration is possible differences in risk between those who did and did not undergo transplantation, leading to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…This organism appears to be a more virulent species and shows a high degree of resistance to various antibiotics [6]. Several reports indicated that N. farcinica commonly infects the respiratory tract, it can also spread through the bloodstream, leading to bacteremia, and infection of the central nervous system (CNS) and soft tissue, which greatly increases morbidity and mortality [7,8]. Furthermore, N. farcinica infection has non-speci c clinical manifestations and is often neglected in the clinical laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Despite their reputation as opportunists, recent studies have shown that one-third of all nocardiosis cases occur in immunocompetent patients. 2 Nocardia are ubiquitous environmental bacteria and are closely related to other well-known soil bacteria, such as Streptomyces. While streptomycetes are known for their ability to produce bioactive secondary metabolites (SMs), with >8400 known compounds in the Dictionary of Natural Products, 3 Nocardia have been relatively understudied by comparison, with only 380 known compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The genus Nocardia comprises a group of opportunistic pathogens of humans and animals. These organisms can cause severe invasive and metastatic disease, particularly in immunocompromised individuals, and can require up to 12 months of antibiotic treatment. , Despite their reputation as opportunists, recent studies have shown that one-third of all nocardiosis cases occur in immunocompetent patients Nocardia are ubiquitous environmental bacteria and are closely related to other well-known soil bacteria, such as Streptomyces.…”
Section: Introductionmentioning
confidence: 99%